2004
DOI: 10.1021/bi0483559
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Differentiation of Three Groups of Tyrosine Residues by Acetylation of N-Acetylimidazole in Manganese Stabilizing Protein

Abstract: To study its contribution to the assembly of the green plant manganese stabilizing protein (MSP) into photosystem II (PSII), tyrosine residues were specifically acetylated using N-acetylimidazole (NAI). In soluble MSP, three groups of Tyr residues could be differentiated by NAI acetylation: approximately 5 (actually ∼5.2) Tyr residues could be easily acetylated (superficial), 1-2 Tyr residues could be acetylated when the NAI concentration was sufficiently high (superficially buried), and 1-2 Tyr residues could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…The absence of Trp and Tyr signals suggests that the environment around W241 and Y242 in C28A,C51A MSP has become more hydrophilic. This is consistent with the report of Zhang et al (2005) who have shown that one Tyr in MSP is resistant to modification by N-acetylimidazole unless the protein is first unfolded in 8 M urea. Uversky et al (2000) have shown that a defining property of intrinsically disordered proteins is the ratio of charged to hydrophobic residues in their primary amino acid sequences.…”
Section: Discussionsupporting
confidence: 93%
“…The absence of Trp and Tyr signals suggests that the environment around W241 and Y242 in C28A,C51A MSP has become more hydrophilic. This is consistent with the report of Zhang et al (2005) who have shown that one Tyr in MSP is resistant to modification by N-acetylimidazole unless the protein is first unfolded in 8 M urea. Uversky et al (2000) have shown that a defining property of intrinsically disordered proteins is the ratio of charged to hydrophobic residues in their primary amino acid sequences.…”
Section: Discussionsupporting
confidence: 93%
“…A huge number of biochemical experiments have been conducted involving site-directed mutagenesis and chemical modification of isolated MSP from several species Eaton-Rye 2005;Han et al 1994;Miura et al 1997;Popelkova et al 2003b;Seidler 1996a;Zhang et al 2005). These studies have identified regions and individual residues of the MSP involved in binding to the intrinsic proteins of PSII.…”
Section: Mutagenesis Of Proposed Binding Sequences Involved In Interamentioning
confidence: 99%
“…Modification of the extrinsic 23 kDa protein with NAI was carried out according to previous reports [20].…”
Section: Modification With Naimentioning
confidence: 99%